Introgression of an adult-plant powdery mildew resistance gene Pm4VL from Dasypyrum villosum chromosome 4V into bread wheat - Yi Wei; Ting Zhang; Yinyu Jin; Wen Li; Lingna Kong; Xiaoxue Liu; Liping Xing; Liping Xing; Aizhong Cao; Aizhong Cao; Ruiqi Zhang; Ruiqi Zhang (Frontiers in Plant Science, 2024)
Powdery mildew caused by Blumeria graminis f. sp. tritici (Bgt) seriously threatens wheat production worldwide. It is imperative to identify novel resistance genes from wheat and its wild relatives to control this disease by host resistance. Dasypyrum villosum (2n = 2x = 14, VV) is a relative of wheat and harbors novel genes for resistance against multi-fungal diseases. In the present study, we developed a complete set of new wheat-D. villosum disomic introgression lines through genomic in situ hybridization (GISH), fluorescence in situ hybridization (FISH) and molecular markers analysis, including four disomic substitution lines (2n=42) containing respectively chromosomes 1V#6, 2V#6, 3V#6, and 6V#6, and four disomic addition lines (2n=44) containing respectively chromosomes 4V#6, 5V#6, 6V#6 and 7V#6. These lines were subsequently evaluated for their responses to a mixture Bgt isolates at both seedling and adult-plant stages. Results showed that introgression lines containing chromosomes 3V#6, 5V#6, and 6V#6 exhibited resistance at both seedling and adult-plant stages, whereas the chromosome 4V#6 disomic addition line NAU4V#6-1 exhibited a high level of adult plant resistance to powdery mildew. Moreover, two translocation lines were further developed from the progenies of NAU4V#6-1 and the Ph1b mutation line NAU0686-ph1b. They were T4DL·4V#6S whole-arm translocation line NAU4V#6-2 and T7DL·7DS-4V#6L small-fragment translocation line NAU4V#6-3. Powdery mildew tests of the two lines confirmed the presence of an adult-plant powdery mildew resistance gene, Pm4VL, located on the terminal segment of chromosome arm 4V#6L (FL 0.6-1.00). In comparison with the recurrent parent NAU0686 plants, the T7DL·7DS-4V#6L translocation line NAU4V#6-3 showed no obvious negative effect on yield-related traits, providing a new germplasm in breeding for resistance.